Armed Non-State actors and state failure: failing international law or failure of international law - Santuraki, Suleiman Usman (Penerbit Universiti Kebangsaan Malaysia, 2019)
Armed Non-State actors are groups involved in the use of force against states or within themselves under several guises including the right to self-determination. The activities of such groups have over the years led to the failure of several states across the globe, which on the other hand results in dire human and material consequences. As a result, the question has often been asked as to why such armed non-state actors thrive especially in the 21st century, notwithstanding the prominence of international law. Is it that international law has failed in regulating such groups, or that the regulation has in it some inherent weaknesses which encourage their proliferation. This paper examines the role of non-state actors in state failure with reference to a few selected cases, to see how activities presented as emancipatory lead to human devastation. It also explores the international legal regime on non-state actors with a view to see if it encourages the emergence of violent groups in the form of national liberation movements. Using doctrinal methodology, the paper analyses both primary and secondary sources of data, relevant literature, and case law on the topic. It finds that the proliferation of the activities of these groups who destroy the essence of statehood, may not be unconnected with the contemporary reality of the legal regime in international law.